Validity and reliability of a locomotor stage-based functional rating scale in spinal cord injury - Maurer-Burkhard, Barbara; Smoor, Imke; Reumont, Anne von; Stierle, Irma; Rupp, Rüdiger; Schuld, Christian (Spinal cord, 2016)
Study design:This is a prospective observational cohort study.Objectives:The objectives of this study were to apply and adapt a rating scale based on locomotor stages (LSs) derived from cerebral palsy (CP) to spinal cord injury (SCI) and to quantify its inter-rater reliability and construct validity.Methods:The inter-rater reliability of LSs originally developed for children with CP was tested in a chronic SCI cohort. On the basis of the distribution of the LSs for CP, Locomotor Stages in Spinal Cord Injury (LOSSCI) were defined. Their validity was then tested with the Spinal Cord Independence Measure (SCIM) in another acute SCI cohort.Results:The 10-point LSs for CP were assessed by two raters in 65 chronic patients. Weighted Cohen’s kappa (WCk) was 0.985 (P<0.0001). Only four mismatches were found, resulting in an accuracy of 93.4%. On the basis of the distribution of the LSs for CP in SCI, the five-point LOSSCI grading scale was developed. WCk of LOSSCI was 0.976 (P<0.0001). Only three mismatches between raters were found, resulting in an overall accuracy of 95.1%. The validity data sets consisted of 448 SCIM records from 161 patients obtained within the first year after injury. Spearman’s correlation coefficients were the highest between LOSSCI and SCIM indoor mobility (room and toilet; R=0.82) and the lowest between LOSSCI and SCIM respiration and sphincter management (R=0.68).Conclusion:LOSSCI provides a reliable and valid clinical tool to assess locomotor function in SCI. LOSSCI not only reflects bipedal walking but also covers a wide range of key motor skills.
Gesehen am 06.12.2018